Od propedeutyki pediatrii do gastroenterologii dziecięcej w Instytucie Pediatrii w Poznaniu (1968-2003). Cz. 1. Zakład Propedeutyki Pediatrii (1968-1990) - Krawczyński, Marian (Pediatria Polska - Polish Journal of Paediatrics, 2017)
Propedeutics of pediatrics as an element of medical studies programme is presented. Its educational and scientific role and activity of Pediatric Propedeutics Department in Poznań (Poland) in 1968-1990 are described. Evolution to Department of Pediatric Gastroenterology and Metabolic Diseases is also documented.